Análise crítica da eficácia da educação à distância: estudo de caso no mercado segurador - Vieira, Andrea Guerra (2012)
This paper develops a research about the use of distance learning in the organizational context. It evaluates the efficacy of this strategy oriented to business partners. Theoretical reference focus on e-learning, one of the most dynamic categories of EAD, directed to the employees of these organizations. It analyses the efficacy of this process developed by an insurer and its business partners, comprehended by brokerages, insures and insurance regulators nationwide. This research adopted exploratory case study method and results were analyzed not only in quantitative but also in qualitative way. Results identify critical aspects related to the main objective, especially concerning the tools for the measurement presented. Although the perception of the people involved is positive to the adhesion to improvement through e-learning, measurement tools used showed variables that must be deeply studied as they impact on the analysis of the efficacy of the distant training in this case